Routes to embodiment - Körner, Anita; Topolinski, Sascha; Strack, Fritz (Frontiers in Psychology, 2015)
Research on embodiment is rich in impressive demonstrations but somewhat poor in comprehensive explanations. Although some moderators and driving mechanisms have been identified, a comprehensive conceptual account of how bodily states or dynamics influence behavior is still missing. Here, we attempt to integrate current knowledge by describing three basic psychological mechanisms: direct state induction, which influences how humans feel or process information, unmediated by any other cognitive mechanism; modal priming, which changes the accessibility of concepts associated with a bodily state; sensorimotor simulation, which affects the ease with which congruent and incongruent actions are performed. We argue that the joint impact of these mechanisms can account for most existing embodiment effects. Additionally, we summarize empirical tests for distinguishing these mechanisms and suggest a guideline for future research about the mechanisms underlying embodiment effects.